Hubungan Aktivitas Fisik Dan Frekuensi Fast Food DenganKejadian Overweight Pada RemajaDi Smp N 5 Karanganyar - Aminin, Fauyan; , Elida Soviana, S.Gz., M.Gizi; , dr.Listiana Dharmawati S.,M.Si (2016)
Introduction: Physical activity has a role on the incidence of overweight along with the development of technology at this point that makes the casual lifestyle for all-round so that the body moves slightly easier to perform everyday activities. Another factor is the consumption of fast food is a food that contains high energy and high in fat but little in vitamin or mineral. Consumption of carbohydrates that exceed the needs will be stored as glycogen and fat. Excess intake of carbohydrates can cause overweight. Objective: This study aimed to find the relationship between physical activity and frequency of fast food with the incidence of overweight in adolescents. Methods: This study used cross-sectional sampling using proportional random sampling method and sample size of 80 respondents at SMP N 5 Karanganyar. Statistical analysis was performed using Chi-square correlation test and Odd Ratio (OR). Results: The research subjects in 40 respondents overweight and 40 non overweight respondents obtained 40 respondents who have physical activity as much as 76.2% of mild and non overweight respondents as mch as 21.1% while non overweight respondents who have a frequency of fast food by category often as much as 39.2% and the overweight respondents who have a frequency of fast food by category often as much as 60.8%. The results of the chi-square test of physical activity with overweight incident stating that there is a relationship between physical activity with the incidence of overweight (p = 0.001; r = 0.073). There is also a relationship between the frequency of fast food with the incidence of overweight (p = 0.010; r = -3444). Conclusion: Based on this study it can be concluded that there relationship physical activity with the incidence of overweight in adolescents so did the frequency of fast food has a relationship with the incidence of overweight in adolescents.